Fiber-based surface plasmon resonance sensor for lead ion detecion in aqueous solution - Suhailin, Fariza Hanim; Alwahib, Ali Abdulkhaleq; Mustapha Kamil, Yasmin; Abu Bakar, Muhammad Hafiz; Huang, Nay Ming; Mahdi, Mohd Adzir (Springer, 2020)
Maghemite/reduced graphene oxide nanocomposite has been successfully deposited onto the surface of a gold-coated Dshaped optical fiber. The synergetic combination of gold, graphene, and iron oxide nanoparticles has shown enhancement of the resonance field and sensitivity of the fiber-based plasmonic sensor. Im particular, the sensor exhibited its capability to detect lead ions (Pb2+) in aqueous solution via monitoring the spectral response of the sensor probe to different concentrations of Pb2+. A sensor sensitivity of 1.2 nm per μg/L was attained at the lowest detected Pb2+ concentration, which is 0.001 ppm (limit of detection). This robust, compact, and highly sensitive fiber-based plasmonic sensor will be of a great interest for an in situ and real-time water safety environmental monitoring.